Anticipating service withdrawal: young people in spaces of neoliberalisation, austerity and economic crisis. Issue 4 (19th August 2016) - Horton, John
Abstract : This paper considers some key impacts of public sector neoliberalisation and austerity measures for everyday geographies of childhood and youth in England. The paper develops three claims, with reference to qualitative research conducted at a youth group in 2007, 2009 and 2013. First, I outline a range of ways in which long‐run processes of public sector neoliberalisation, and more abrupt cuts to public sector expenditure 'in the current climate' of austerity politics, have substantially transformed geographies of childhood and youth in many minority world contexts. However, I argue that extant research on these transformations has tended to reproduce some rather partial understandings of impacts of service withdrawal, which I critique via a reading of recent geographical work on anticipatory politics. Second, I evidence how political‐economic contexts of neoliberalisation and austerity have constituted a particular atmosphere and sense of the future, tangibly affecting everyday relationships, spaces and the efficacy of service provision at the case study youth group. In particular, I emphasise the significance of anticipated futures, noting that the anticipation of funding cuts is having manifold everyday, lived consequences that are arguably more wide‐ranging, intractable and troubling than the impacts of funding cuts themselves. Third, in particular, I argue that spaces of anticipated funding cuts and service withdrawal are frequently characterised by an intensification of anxieties about, and hopes for, young people's futures. I note that young people are diversely affected by, and engaged in, the circulation of these anxieties and hopes – but also recognise that young people's geographies go on, and sometimes offer hopeful ways on, 'in the current climate'.